Ekspresi protein P53 pada hiperplasi prostat benigna, prostatic intraepithelial neoplasia dan adenokarsinoma prostat - Irianiwati, Irianiwati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: The mutant type of p53 protein looses its ability to inhibit cell proliferation and the increase of this protein expression has been detected among several human cancers. The p53 mutant protein is stable and therefore can be detected by immunohistochemical technique. The over expression of p53 in the several prostatic lesions has widely been investigated but the result is still controversial. The relation between p53 expression with the histological grading of the prostatic lesions is still unclear.Objective: To study the correlation between p53 expression with the histological grading of the prostatic lesions.Methods: Sixty two paraffin blocks of specimens which were diagnosed as benign prostate hyperplasia, prostatic intraepithelial neoplasia, and adenocarcinoma of the prostates collected from several anatomic pathology laboratories in 'Yogyakarta were chosen. Specimens containing heavy inflamatory cells and necrotic tissues were excluded from this study. The chosen specimens were reexamined and histological malignant grading were also determined. The specimens were then stained with p53 MoAb-DO-7 (DAKO) immunohistochemically and the score of p53 positive cells, p53 intensity, the distribution of p53 positive cells, and total expression of p53 were determined among them. The correlation between malignant grading and those scores were analyzed by defining the correlation coefficient of Spearman.Results: There was a weak significant correlation